STRATEGI PEMASARAN HHBK GULA AREN DI DEASA LUMPIAS WILAYAH KPHL MINAHASA UTARA - Marthinus Fatemyo; Hengk D. Walangitan; Wawan Nurmawan (COCOS, 2018)
Abstract This study aims to describe and analyze the marketing strategy of palm sugar in Lumpias Village. The study was conducted in September 2017 using a survey approach by interviewing 6 producers of respondents through questionnaires, with open questions. The data obtained were analyzed using the SWOT method. Based on the results of the SWOT analysis obtained hold and maintain strategy means that the marketing of palm sugar in Lumpias Village has the strength and opportunity to continue to be maintained and maintained through market penetration and product development. Furthermore, in the development of marketing with the following strategies : (1) the strategy of building and increasing business partnership and expanding the marketing network by utilizing the development of information technology (2) the strategy of promoting through the internet (3) the strategy of maintaining and improving product quality Key words: HHBK Marketing Strategy Palm Sugar in Deasa Lumpias North Minahasa KPHL Region.